The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0182730
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying immediate and delayed effects of anthelmintic exposure on ecosystem functioning supported by a common dung beetle species

Abstract: Dung beetles (Coleoptera: Scarabaeoidea) support numerous ecosystem functions in livestock-grazed pastures. Exposure to veterinary anthelmintic residues in livestock dung can have lethal and sublethal effects on dung beetles, and can reduce rates of dung removal, but the immediate and longer-term consequences for other dung beetle mediated functions have rarely been studied. We investigated the consequences of anthelmintic exposure on survival of the dung beetle Aphodius fossor and its delivery of four ecosyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
2
22
0
1
Order By: Relevance
“…Over a period of 36 weeks, mixed species assemblages of Aphodius and Onthophagus dung beetles were shown to achieve the highest cattle dung decomposition rates in comparison to monoculture treatments, when the biomass of beetles was standardised (Beynon et al, 2012). A similar conclusion was reached in a study by Manning et al (2017) where the dung-removing capacity of Aphodius ater (De Geer), Aphodius fossor (L.) and…”
Section: Discussionsupporting
confidence: 67%
“…Over a period of 36 weeks, mixed species assemblages of Aphodius and Onthophagus dung beetles were shown to achieve the highest cattle dung decomposition rates in comparison to monoculture treatments, when the biomass of beetles was standardised (Beynon et al, 2012). A similar conclusion was reached in a study by Manning et al (2017) where the dung-removing capacity of Aphodius ater (De Geer), Aphodius fossor (L.) and…”
Section: Discussionsupporting
confidence: 67%
“…Thus, metrics of multifunctionality often qualitatively reflected the positive or negative responses of some single functions, while other single functions showed an opposite response or no response (Alsterberg et al, ; Antiqueira et al, ; Bradford et al, ; Ramus et al, ). The inverse was also observed, whereby global change drivers affected some single functions but not others, producing no discernible overall effects on EMF (Alsterberg, Sundback, & Gamfeldt, ; Manning et al, ). In contrast, others found that nearly all single functions responded in the same manner, which was inevitably reproduced in the multifunctionality metric (Chandregowda, Murthy, & Bagchi, ; Luo et al, ; Quero et al, ).…”
Section: Insights From Single and Multiple Functions: Seeing The Forementioning
confidence: 99%
“…Abiotic and biotic components interact with each other, for example, through the impact of soil compaction on plant roots and nutrient uptake global change on EMF (Liu et al, 2017;Robroek, Jassey, & Hefting, 2017;Zhang, Eldridge, & Delgado-Baquerizo, 2016). Importantly, other studies considered it vital to understand (or just summarize) the complex trade-offs and interactions that occur among global change drivers and multiple functions, for example, when functions are not correlated with each other (Birkhofer et al, 2018;Luo et al, 2018;Manning, Beynon, & Lewis, 2017;Vandandorj, Eldridge, Travers, & Delgado-Baquerizo, 2017;Zhang et al, 2016).…”
Section: Applying Ecosystem Multifunctionality To Global Change Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…()) dung removal is not always positively linked to other ecosystem functions. For instance, while dung removal by the dung beetle Aphodius fossor was negatively affected by 0.5 mg kg −1 exposure to ivermectin, exposure had no significant effect on three other relevant ecosystem functions (Manning et al ., ). While our results suggest that flies have a limited importance for dung removal compared with beetles, their importance may be much more significant when considering other pasture‐relevant ecosystem functions.…”
Section: Discussionmentioning
confidence: 97%